Lackawanna blues - Ndegeocello, Meshell 1969- (HBO Video, 2005)
In a story fueled by rhythm and blues, a young boy's life is shaped by love and the stories of a cast of characters in the boarding house where he lives. Based on Ruben Santiago-Hudson's autobiographical play about his relationship with his guardian Rachel Crosby, set in 1950's and 1960's Lackawanna, New York. After the separation of his parents, young Ruben, a part-black, part-Hispanic child, is sent to live in a small-scale boarding house run by the kind-hearted "Nanny" Crosby and her younger husband Bill